FINDING GRAMMATICAL ERRORS IN THE DESCRIPTIVE TEXT WRITTEN BY THE EIGHTH GRADERS OF SMP MARKUS MEDAN - Marlina Surya Indriani; Ance Rosario Siallagan; Lasmaida Nainggolan; Sondang Manik; Lastri Wahyuni Manurung (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Abstract This research entitled "Finding Grammatical Errors in The Descriptive Text Written by The Eighth Grade of SMP Markus Medan". This research describes about grammatical errors in written descriptive text. For getting the data for this research, the research is taken from the eighth graders of SMP Markus Medan. The methods of research used are qualitative method. Qualitative method is used to answer the problem that is types of grammatical errors in written descriptive text. Based on the problems, it is found ten grammar errors that occur in descriptive text such as to be, auxiliary verb, pronoun, verb, word order, degree of comparison, conjunction, spelling, punctuation, and capitalization.